Faktor-faktor yang mempengaruhi penjualan umkm berbasis ekonomi kreatif di Kota Jambi - Natalisa, Rica; Amir, Amri; Zulfanetti, Zulfanetti (Jurnal Paradigma Ekonomika, 2022)
This study aims to analyze the factors that influence the sales of MSMEs based on the Creative Economy in Jambi City. This research was conducted in Jambi City from July to September 2020. The selection of research locations was carried out purposively by choosing one of the creative economy-based SMEs in Jambi City, namely the food creative industry. The data used are primary data and secondary data and analyzed using multiple linear regression analysis. The results of this study indicate that the t value of the credit variable is 3.812 < t table 1.665 so that H0 is rejected and H1 is accepted. If viewed from the MSME credit Prob of 0.000 because Prob > 0.05 then H0 is rejected and H1 is accepted. This shows that credit has an effect on sales of MSMEs in Jambi City. The t value of the asset variable is 2.271 < t table 1.665 so that H0 is rejected and H1 is accepted. If viewed from the asset Prob of 0.025 because Prob > 0.05 then H0 is rejected and H1 is accepted. This shows that assets have an effect on the sales of MSMEs in Jambi City. While the t value of the Initial Capital variable is 0.507 and the t table is 1.665 so that the value of t count < t table, it means that H0 is accepted and H1 is rejected. If viewed from the Prob of R of 0.613 because Prob> 0.05 then H0 is accepted and H1 is rejected. This shows that initial capital has no significant effect on sales of MSMEs in Jambi City.